Pemikiran Hamka Tentang Moral - Sudin Sudin (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
This article explores Hamka’s idea on Moral Philosophy. Hamka serves both as Ulema and philosopher on Moral Philosophy in particular. His Moral Philosophy seems distinctive in both rationality and religiosity. Hamka’s Moral Philosophy is based on Islamic teachings or the Oneness of God (Tauhid). Tauhid is, in Hamka’s view, a source of moral. One’s virtues or evil, according to Hamka, is influenced by the dignity of Faith to God.